2010
DOI: 10.1016/j.anai.2010.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of systemic reactions to subcutaneous immunotherapy injections: year 1 outcomes of the ACAAI and AAAAI Collaborative Study

Abstract: We demonstrated the feasibility of annual surveillance of SRs associated with SCIT injections. This surveillance study will continue to monitor SCIT adverse events in parallel with vigorous efforts instituted by members of professional organizations aimed at reducing the risk of severe reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 15 publications
3
47
0
2
Order By: Relevance
“…Most reactions were considered mild, and death due to SCIT was rare (ie, incidence is about one per million to one per 2 million injections). 36,84 As far as safety of SCIT in AR, the most recent Cochrane review found that epinephrine was administered in 0.13% of injections in the treated group compared with 0.01% in the placebo group, with no fatalities reported. Local reactions were common in the treated group compared with placebo (92% vs 33%), with the majority not requiring any additional treatment.…”
Section: The Effect Of Slit In Armentioning
confidence: 99%
“…Most reactions were considered mild, and death due to SCIT was rare (ie, incidence is about one per million to one per 2 million injections). 36,84 As far as safety of SCIT in AR, the most recent Cochrane review found that epinephrine was administered in 0.13% of injections in the treated group compared with 0.01% in the placebo group, with no fatalities reported. Local reactions were common in the treated group compared with placebo (92% vs 33%), with the majority not requiring any additional treatment.…”
Section: The Effect Of Slit In Armentioning
confidence: 99%
“…[30]. However, subcutaneous immunotherapy (SCIT) is associated with a significant risk of severe adverse events [37,38]. Thus, efforts have been done towards alternative routes (local and noninjection) for allergen delivery [39].…”
Section: Mechanisms Of Allergen-specificmentioning
confidence: 99%
“…However, current approaches show limitations concerning the long-term efficacy and safety due to local side effects and risk of anaphylaxis. Effective and safe vaccines require the use of effective and safe adjuvants [20][21][22][23]. Therefore, this paper provides an overview of the currently adjuvants used for allergen immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…With conventional immunotherapy, the rates of severe systemic reactions are probably Ͻ1%, whereas with rush immunotherapy reported reaction rates have been in some instances Ͼ30%. [6][7][8][9] In addition, as with any adverse reaction to a therapeutic agent, reporting rates are probably not completely trustworthy. Also, response rates to surveys designed to assess incidence are usually, low, Ͻ30%.…”
Section: Incidencementioning
confidence: 99%